Harmonization Problems of the education systems indicators in the BriCs Countries - D. Yampolskaya; A. Korneeva; H. Cai; B. Campolina (BRICS Law Journal, 2019)
The conditions for the development of modern states are impossible without cooperation and integration with other states in various socio-economic areas. The formation and protection of an alternative position in the world by a number of countries led to the creation of the BRICS association. Participation in this association is of great importance for Russia in a variety of fields. One of the promising areas of cooperation is the sphere of education in all its aspects, ranging from preschool education to the attainment of various degrees and titles. This article addresses the issue of coordination of the BRICS countries in the field of education.The basis for determining the indicators of the education systems and the principles of their comparison was the similar data from the international organizations UNESCO, OECD and Eurostat. As a result of studying the principles of collecting statistical data and methodological materials for comparing the education sector indicators in these international organizations, a certain vision of the database of the BRICS countries has been set. On the one hand, this base should not contradict international practice; on the other hand, the chosen indicators should be used by all countries of the BRICS association. Following this study, a proposal on the principles of information collection was made, as well as a proposal on the main indicators for education indicators comparison in the BRICS countries.The basis for cooperation between the education systems is a harmonized system of concepts and definitions, which allows unambiguous interpretation of such fundamental terms as education, educational program, educational institution, student, entrant, acceptance for study programs, graduates, graduations, personnel of educational institutions, expenses for education, etc.In parallel with the harmonization of the education system terminology, it is necessary to harmonize statistical indicators that can quantify the education system at all levels. As arule, observation units of education statistics are institutions that provide educational services at all levels of education to both individuals and legal entities.